Pengembangan model induktif dalam pembelajaran apresiasi puisi - Warsiman, Warsiman (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This research was conducted to improve students’ ability to appreciate poetry through the use of the Inductive Model. This study applied a modified Research and Development method, and the results were analyzed descriptively. The results reveal that the use of the Inductive Model is able to improve students’ ability in appreciating poetry by implementing eight instructional steps. The numerical improvement can be seen in the students’ average scores in each treatment. In the first treatment, the students’ average score was 60.9; in the second treatment, it increased to 62.4; and in the third treatment, it reached 65.3. Based on the criteria of success, the students’ average scores show a consistent increase from the first to the third treatment, progressing from a fair level to a very good level. Specifically, the first treatment shows an increase from a fair level to an excellent level, the second treatment shows an increase from a good level to a very good level, and the third treatment shows an increase from a very good level to an excellent level.